Adaptive plasticity and diurnal rhythm in the primate spinal stretch reflex are independent phenomena. - Jonathan Wolpaw; Noonan, P. A.; O'Keefe, J. A. (Brain research, 1984)
Recent studies have revealed two phenomena producing considerable variation in amplitude of the initial, purely segmental, largely monosynaptic, response to sudden muscle stretch, the spinal stretch reflex (SSR), without change in background EMG activity or initial muscle length. The first is small and short-term, a modest diurnal rhythm in SSR amplitude. The second is large and long-term, marked adaptive change in SSR amplitude which occurs gradually over weeks and months when animals are rewarded for such change. This second phenomenon may involve persistent segmental alteration, and, if so, could constitute a technically accessible substrate of memory. The present study compared the two phenomena and sought evidence of interaction between them. The diurnal rhythm persisted, without change in phase and with only minimal change in amplitude, despite the occurrence of marked adaptive change. Animals did not utilize the rhythm to increase reward percentage by altering daily performance schedules. These results suggest that the mechanisms of the diurnal rhythm and of adaptive plasticity in SSR amplitude are separate and independent. The diurnal rhythm's effect on movement was not altered by adaptive change in SSR amplitude. This effect was comparable to adaptive change's effect on movement when both were expressed as change in movement/change in SSR amplitude.
Keywords: adaptive plasticity; diurnal rhythm; Learning; Memory; primate; stretch reflex